Residential segregation and socio-spatial processes in Marseille. Urban social sustainability challenge - Grzegorczyk Anna (Bulletin of Geography. Socio-Economic Series, 2021)
The aim of the study is to determine the scale and patterns of the social segregation of Aix-Marseille-Provence Metropolis and Marseille, in the light of the socio-spatial processes it is currently undergoing and its influence on social sustainability. In the study, quantitative measures of segregation are confronted with a qualitative interpretation of existing facts gathered during literature analysis and field observations. Population groups most subject to residential segregation are revealed, together with the areas of the greatest concentration of particular population categories. Changes of concentration pattern in the decade 2007–2017 are indicated and the role of gentrification and privatiszation of land, which are all conditioned in Marseille by the city's economic restructuring, liberal housing policy and historical role of the port-industrial system.